INTENSIFIKASI PENDIDIKAN ISLAM PADA MASYARAKAT PLURAL UNTUK MENGANTISIPASI POTENSI KONFLIK SOSIAL HORIZONTAL BERNUANSA SARA MELALUI JALUR NONFORMAL DI KABUPATEN INDRAGIRI HULU - Juni Erpida Nasution (STAI Nurul Falah Airmolek, 2020)
Islam according to the majority of its adherents is a holistic religion. Islam is not only defined as a mere religion of monotheism, but teachings concerning all aspects of life, public religion, religious pluralism is not just a matter of accommodating religious truth claims in the private sphere, but also a matter of public policy where Muslim leaders must recognize and protect religious freedom. , not only intra-Muslims, but also between religions and religions that teach divinity and humanity, including the issue of pluralism. Pluralism is something that is born from the proposition of divine teachings. Reason concludes that if oneness only belongs to Allah, then other than Him is not worthy to bear it which means other than Allah is plurality. Plurality and diversity in terms of religion,tradition, art, culture, way of life, and the values held by ethnic groups of Indonesian society. On the one hand, this diversity and plurality for Indonesia can be a positive and constructive force. On the other hand, it will be a negative and destructive force if it is not directed positively